Rosacea pathogenesis and topical treatment options – a review - Okońska, Aleksandra; Kozakiewicz, Julia; Ziemba, Michał; Kałuska, Joanna; Suprun, Tomasz; Sokół, Aleksandra; Mościszko, Klaudia; Nowicka, Katarzyna; Klimek, Wiktor; Majewska, Maria (Quality in Sport, 2025)
Introduction: Rosacea is a chronic inflammatory condition primarily affecting the central facial areas and eyes, with subtypes including erythematotelangiectatic, papulopustular, phymatous, and ocular rosacea. While not life-threatening, rosacea significantly impacts quality of life, contributing to psychological distress. Materials and methods: This article reviews the pathogenesis and treatment of rosacea, incorporating data from PubMed, Google Scholar, and Web of Science using keywords such as “rosacea,” “Demodex,” “topical treatment,” and “pathogenesis.” Summary: Rosacea is driven by multifactorial mechanisms, including neurovascular hyperreactivity, immune system dysregulation, sebaceous gland dysfunction, microbial imbalances, and genetic predisposition. Triggers like UV radiation, stress, and certain foods exacerbate symptoms by activating pathways such as transient receptor potential (TRP) channels and inflammatory mediators like IL-6 and TNF-α. Effective treatments focus on symptom management and include topical agents like ivermectin, metronidazole, azelaic acid, calcineurin inhibitors, retinoids, alpha-adrenergic receptor agonists and sodium sulfacetamide. These therapies target inflammation, erythema, and microbial factors, with clinical trials demonstrating improvements in erythema, papules, and pustules. Conclusions: While current treatments offer significant relief, the article emphasizes the importance of further research into the underlying mechanisms to develop more advanced therapeutic options.